2019
DOI: 10.1108/jima-03-2019-0058
|View full text |Cite
|
Sign up to set email alerts
|

The impact of PHTPS on trip quality, trip value, satisfaction and word of mouth

Abstract: Purpose The study aims to determine the impact of non-Muslim tourists’ perception of halal tourism products and services (PHTPS) on trip quality, trip value, satisfaction and word of mouth (WOM) towards halal tourism destination. Design/methodology/approach A total of 375 non-Muslim tourists were surveyed in Malaysia using partial least square technique. Findings The findings showed that PHTPS has a significant impact on all four dimensions. The strongest relationship was found between PHTPS and trip quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 70 publications
(119 reference statements)
0
56
1
6
Order By: Relevance
“…Related to tourism, tourist satisfaction refers to the pleasure of tourists after visiting certain destinations. Previous literature has suggested that customer intentions, loyalty and behavior (Kozak and Rimmington, 2000; Chi and Qu, 2008; Chen and Chen, 2010; Su and Hsu, 2013; Battour et al , 2019) and Su et al , 2017) and differences in quality, environment, price and person (Bitner, 1990; Bolton and Drew, 1991) are significant in influencing customer satisfaction. Zeithaml and Bitner (2003) believe that customer satisfaction is a post-purchase experience.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Related to tourism, tourist satisfaction refers to the pleasure of tourists after visiting certain destinations. Previous literature has suggested that customer intentions, loyalty and behavior (Kozak and Rimmington, 2000; Chi and Qu, 2008; Chen and Chen, 2010; Su and Hsu, 2013; Battour et al , 2019) and Su et al , 2017) and differences in quality, environment, price and person (Bitner, 1990; Bolton and Drew, 1991) are significant in influencing customer satisfaction. Zeithaml and Bitner (2003) believe that customer satisfaction is a post-purchase experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is expected to increase in 2018 to 12.7 million workers and increase to 13.0 million workers in 2019”. People always possess the willingness to know about other countries, such as their cultural norms, historical relics, religious practices and exotic locations (Battour et al , 2019). Aware of the economic potential, the Indonesian Government has consistently provided support and incentives for the local tourism industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) recommend that halal industry should also target the enormous size of non-Muslim travelers. In particular, a recent study by Battour et al. (2019) conclude that non-Muslim travelers report lower levels in trip quality, trip value, and word of mouth while traveling to Muslim-friendly destinations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From non-Muslim tourists' perspective, Battour et al (2017) explore their perceptions toward halal tourism in Malaysia and Turkey. Recently, Battour et al (2019) examine the impact of non-Muslim travelers' perception of halal tourism on the quality and value of trip, as well as their satisfaction and word of mouth toward halal tourism destination. However, research on understanding Muslim travelers' behavior and needs while traveling to non-Islamic destinations is limited (Hassani and Moghavvemi, 2019;Nassar et al, 2015;Sriprasert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%